Adaptations to interval training at common intensities and different work:rest ratios - Barzdukas, A.; Franciosi, P.; Trappe, S.; Letner, C.; Troup, J. P. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
Interval training sets are commonly used in competitive swimming programmes. It is unclear, however, how different work:rest ratios used in interval training affect aerobic and anaerobic energy systems. The purpose of this study, therefore, was to determine which work:rest ratio (1:2 or 1:1/2) was more effective in improving 400 m specific race performance. Relative energy delivery (anaerobic vs aerobic) was also examined. Two groups of swimmers participated in five weeks of training with a major set of 10 x 100 freestyle at an intensity of 110% of V0 2 max: Group 1:2 at a work:rest ratio of 1:2, and Group 1:1/2 at a work:rest ratio of 1:1/2. Results indicate that, at the same intensity, a work:rest ratio of 1:2 is more specific to anaerobic work and a work:rest ratio of 1:1/2 is more conducive to aerobic development. Because swimming performance is dependent on optimal anaerobic and aerobic energy delivery, it is recommended that both modes of training be utilized.